Urine Afamin as a biomarker of lupus nephritis - Lin, Shiyu; Du, Mengru; Wang, Jie; Lai, Peng; Yao, Genhong; Chen, Weiwei; Xu, Xue; Sun, Lingyun (Frontiers in Immunology, 2025)
ObjectiveThe association between various biomarkers and the risk of lupus nephritis (LN) has been extensively investigated. However, a dearth of readily available, specific, and sensitive diagnostic biomarkers for LN remains. This study aimed to examine the levels of Afamin in the urine and plasma of patients with systemic lupus erythematosus (SLE) and to evaluate its potential utility for diagnosing LN.MethodsThis study enrolled 31 LN–SLE patients, 31 non-LN–SLE patients, and 27 healthy controls (HC). First, tandem mass tag (TMT)–based proteomic screening of urine and plasma (n = 15 per group) identified Afamin as a significantly upregulated protein in LN. Subsequently, ELISA validation confirmed that both uAfamin and pAfamin levels were markedly higher in the LN group. The diagnostic performance of uAfamin for active LN was further evaluated using receiver operating characteristic (ROC) curve analysis.ResultsLevels of both urinary and plasma Afamin were significantly elevated in patients with LN–SLE compared to those with non-LN–SLE. Moreover, uAfamin and pAfamin levels demonstrated robust correlations with multiple clinical indicators of disease activity, including 24h urinary total protein (24hUTP), creatinine, urea, hematuria, pyuria, SLEDAI, and renal SLEDAI. Multivariable linear regression analysis established uAfamin as an independent determinant of renal SLEDAI scores. Consistent with this, ROC curve analysis confirmed that uAfamin possesses a strong capacity to diagnose LN.ConclusionThe uAfamin level serves as a biomarker for LN, aiding in monitoring disease progression and suggesting a new avenue for personalized treatment strategies.